Ecologia, distribuicao e densidade da alga Melosira italica (Bacillariophyceae: Centricae) na Represa do Lobo (Broa), Estado de Sao Paulo, Brasil - Marins, Marcos de Afonso (Revista de Biología Tropical, 1978)
In a study of the distribution, standing-stock and ecological aspects of Melosira italica in a tropical lacustrine environment, Lobo reservoir (Broa), State of Sao Paulo, Brasil, the alga was found in all the water column and was dominant at all levels. The number of cells in the filament was determined and some environmental factors such as water temperature, dissolved oxygen, water transparency (Secchi disc) and total rainfall were analyzed.